Angle‐based Y‐shaped chipless radio frequency identification tag. Issue 15 (1st December 2015) - Feng, Caixia; Chen, Xinwei; Han, Liping; Li, Li; Han, Guorui; Zhang, Wenmei
Abstract : This study presents a novel angle‐based chipless radio frequency identification tag. Its scatterer is designed to be Y‐shaped. It encodes data using the space angles between the arms of the Y‐shape and is identified by measuring the scattered field in two orthogonal polarisation directions. Even if it is rotated, the tag can be identified. In addition, the tag is excited with a circularly polarised wave. The cases excited with an elliptically polarised wave are also discussed. Finally, the proposed tag is realised and measured. The results indicate the realised tags operate in the frequency range 1.4–1.8 and 2.1–2.5 GHz for different codes. Every element can carry 8.1 bits of coding information. The identification errors are less than ±3.8°.